Transcriptional profiling and immunophenotyping show sustained activation of blood monocytes in subpatent Plasmodium falciparum infection. Issue 6 (18th June 2020) - Loughland, Jessica R; Woodberry, Tonia; Field, Matt; Andrew, Dean W; SheelaNair, Arya; Dooley, Nicholas L; Piera, Kim A; Amante, Fiona H; Kenangalem, Enny; Price, Ric N; Engwerda, Christian R; Anstey, Nicholas M; et al.
Abstract: Objectives: Malaria, caused by Plasmodium infection, remains a major global health problem. Monocytes are integral to the immune response, yet their transcriptional and functional responses in primary Plasmodium falciparum infection and in clinical malaria are poorly understood. Methods: The transcriptional and functional profiles of monocytes were examined in controlled human malaria infection with P. falciparum blood stages and in children and adults with acute malaria. Monocyte gene expression and functional phenotypes were examined by RNA sequencing and flow cytometry at peak infection and compared to pre‐infection or at convalescence in acute malaria. Results: In subpatent primary infection, the monocyte transcriptional profile was dominated by an interferon (IFN) molecular signature. Pathways enriched included type I IFN signalling, innate immune response and cytokine‐mediated signalling. Monocytes increased TNF and IL‐12 production upon in vitro toll‐like receptor stimulation and increased IL‐10 production upon in vitro parasite restimulation. Longitudinal phenotypic analyses revealed sustained significant changes in the composition of monocytes following infection, with increased CD14 + CD16 − and decreased CD14 − CD16 + subsets. In acute malaria, monocyte CD64/FcγRI expression was significantly increased in children and adults, while HLA‐DR remained stable. Although children and adults showed a similar pattern of differentially expressed genes, the number and magnitude of gene expression change were greater in children. Conclusions: Monocyte activation during subpatent malaria is driven by an IFN molecular signature with robust activation of genes enriched in pathogen detection, phagocytosis, antimicrobial activity and antigen presentation. The greater magnitude of transcriptional changes in children with acute malaria suggests monocyte phenotypes may change with age or exposure. Abstract : We investigate the transcriptional, functional and phenotypic changes in monocytes during an experimental blood‐stage P. falciparum infection in malaria naive healthy subjects and during an episode of clinical malaria in children and adults residing in a malaria‐endemic region. We specifically isolated monocytes for transcriptome analysis by RNA sequencing, to determine monocyte gene expression during subpatent and clinical malaria. Monocyte activation during subpatent malaria is driven by an inflammatory molecular signature and a greater magnitude of transcriptional changes in children with acute malaria suggest monocyte phenotypes may change with age or exposure.